Ανατροπή ισορροπιών στα στενά: Η μυστική συμφωνία της Κωνσταντινουπόλεως του 1915 - Βισβίζη-Δοντά, Δόμνα (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
No sooner the question of the eastern Aegean Islands remained unsettled at Bucarest in 1913, than the Russians suspected a Greek expansion over the Straits and Constantinople, with the tacit approval of Britain. This expansion seemed more certain, when, at the outbreak of the Great War, the Turks closed the Straits and isolated Russia: The British proposed to use Greek troops and ships for an attack on Gallipoli. This raised the old ghost of a revived Byzantine empire and the Czar made it a sine qua non condition that no Greek forces should participate in an attack on the Straits, or in any settlement concerning that question. He demanded that the Straits and the adjoining territory be included within his empire. Neither the British, nor the French, or the Greeks wished to see the Czar seated on the Bosphorus. But only when the Russians threatened to withdraw from the alliance, did Britain and France agree to Russia’s claims on condition «that the war was carried to a victorious conclusion ». The abortive secret treaty of Constantinople of 1915 was formally concluded at the monent when Venizelos, the initiator of the Greek participation in the Straits question, had resigned. Nevertheless, the presence of the Russians in the area was never before that important and played such a principal role as in 1915. But also the presence of the Greeks in that same area neither had nor did become ever again of such a consequence in the history of contemporary Europe.